Analisis Penentuan Status Ketersediaan Air Di Kota Salatiga Berdasarkan Sistem Grid - Rubiantoro, Eko Anton; Susilowati, Indah (Universitas Pendidikan Ganesha, 2025)
The status of water availability is very important in urban planning. The status of water availability will affect the direction of development policy. Calculation of water supply status can be done by utilizing spatial analysis based on a grid system by considering the water needs of the household sector and the land-based economic activity sector. The research was conducted using descriptive methodology with the application of basic physical data overlay analysis techniques with environmental services using ArcGIS 10.8 software. The analysis was conducted by overlaying the grid administration map with the land cover map, calculating the proportion of land cover type weights, calculating the population distribution for each grid, distributing household water demand for each grid, water demand from the land-based economic activity sector, water demand for each grid, and finally the status of water carrying capacity. The Salatiga City grid system uses data provided by P3E Java, Ministry of Environment and Forestry, which is 153.3 meters x 153.3 meters or ± 2.35 Ha. The calculation of water availability in Salatiga City based on the grid system resulted in 250,455,198 m3/year.